Analysis of geological characteristics and potential factors of formation damage in coalbed methane reservoir in Northern Qinshui basin - Hongjian Wu; Xiangwei Kong (Scientific Reports)
Abstract Given the suboptimal physical properties and distinctive geological conditions of deep coalbed methane reservoirs, any reservoir damage that occurs becomes irreversible. Consequently, the protection of these deep coalbed methane reservoirs is of paramount importance. This study employs experimental techniques such as scanning electron microscopy, X-ray diffraction, and micro-CT imaging to conduct a comprehensive analysis of the pore structure, mineral composition, fluid characteristics, and wettability of coal seams 3# and 15# in the northern Qinshui Basin of China. The objective is to elucidate the types of reservoir damage induced by fracturing fluid intrusion along with potential contributing factors. This research is critical for ensuring safe drilling practices, effective gas injection, and efficient development strategies for coalbed methane reservoirs. The findings indicate that the mineral composition of the coal rock consists of 18.52% clay minerals, 34% quartz, and 8.98% calcite. Furthermore, hydrophilicity and natural fractures within the coal rock may lead to water-sensitivity, velocity- sensitivity, alkali- sensitivity, and acid- sensitivity damages to the coalbed methane reservoir. There exists good compatibility between fracturing fluids and both coal rock as well as formation water. The fine particles generated from hydraulic fracturing are prone to transport through the coal seam while obstructing pore throats. Thus exhibiting pronounced velocity sensitivity characteristics in this reservoir type. Coal rock demonstrates pronounced stress sensitivity. As the effective stress escalates from 2 MPa to 10 MPa, there is a marked decrease in the permeability of coal rock. With increasing effective stress, the pore structure and natural fractures within the coal rock are compressed more tightly, resulting in a diminished permeability of the coal rock. When exposed to fracturing fluid saturation, not only does the volume of these particles expand but they can also cause blockages that result in up to a 60% reduction in fracture flow capacity. These insights are vital for optimizing fracturing designs aimed at protecting reservoir integrity.